Potential for strength and endurance training to amplify endurance performance - Hickson, R. C.; Dvorak, B. A.; Gorostiaga, E. M.; Kurowski, T. T.; Foster, C. (Journal of Applied Physiology, 1988)
The impact of adding heavy-resistance training to increase leg-muscle strength was studied in eight cycling- and running-trained subjects who were already at a steady-state level of performance. Strength training was performed 3 days/wk for 10 wk, whereas endurance training remained constant during this phase. After 10 wk, leg strength was increased by an average of 30%, but thigh girth and biopsied vastus lateralis muscle fiber areas (fast and slow twitch) and citrate synthase activities were unchanged. Maximal O2 uptake (VO2max) was also unchanged by heavy-resistance training during cycling (55 ml.kg-1.min-1) and treadmill running (60 ml.kg-1.min-1); however, short-term endurance (4-8 min) was increased by 11 and 13% (P less than 0.05) during cycling and running, respectively. Long-term cycling to exhaustion at 80% VO2max increased from 71 to 85 min (P less than 0.05) after the addition of strength training, whereas long-term running (10 km times) results were inconclusive. These data do not demonstrate any negative performance effects of adding heavy-resistance training to ongoing endurance-training regimens. They indicate that certain types of endurance performance, particularly those requiring fast-twitch fiber recruitment, can be improved by strength-training supplementation.